5, 12‐Dialkyl‐5, 12‐dihydroindolo[3, 2‐a]carbazole‐Based Oxime‐Esters for LED Photoinitiating Systems and Application on 3D Printing. Issue 8 (15th April 2022) - Hammoud, Fatima; Giacoletto, Nicolas; Nechab, Malek; Graff, Bernadette; Hijazi, Akram; Dumur, Frédéric; Lalevée, Jacques
Abstract: In order to expand the application of oxime‐esters (OXEs) and to introduce a one‐component photoinitiating system of high performance in visible light photopolymerization, a series of 5, 12‐dialkyl‐5, 12‐dihydroindolo[3, 2‐a]carbazole‐based oxime‐esters with visible light absorption abilities is designed and synthesized. Notably, when irradiated with light‐emitting diodes at 405 nm, the proposed structures can undergo a direct cleavage of the NO bond followed by decarboxylation, generating free radicals capable to efficiently initiate free radical photopolymerizations (FRP). Furthermore, the new OXEs showed good thermal initiation abilities and can be used as dual photo and thermal initiators. An interesting structure/reactivity/efficiency relationship can be obtained by comparing the reactivity of the different radicals generated upon photoexcitation at identical chromophore but also by comparing the photoinitiating ability of the hexyl derivatives (1)–(10) with that of methyl derivatives (1′)–(10′) characterized by a lower solubility than the previous series in resins. Chemical mechanisms are studied through different techniques including real‐time Fourier transform infrared spectroscopy, UVvisible absorption spectroscopy, fluorescence (time‐resolved or steady‐state) as well as molecular modeling calculations. To finish, OXEs are incorporated in new photosensitive 3D printing resins, furnishing 3D objects with a remarkable spatial resolution. Abstract : In this article, 18 oxime esters based on the 5, 12‐dialkyl‐5, 12‐dihydroindolo[3, 2‐ a ]carbazole scaffold are successfully synthesized and used as novel photoinitiators. Based on their light absorption properties, cleavage ability, decarboxylation reaction as well as the reactivity of the generated radicals, some pertinent structure/efficiency relationships are established and discussed. In addition, a dual thermal photochemical initiator feature is also found.